Enhancing the pressure limitation in large-volume Bridgman-anvil cell used for in situ neutron diffraction. Issue 4 (2nd October 2019) - Hu, Qiwei; Fang, Leiming; Li, Qiang; Li, Xin; Chen, Xiping; Xie, Lei; Zhang, Jiawei; Liu, Fangming; Lei, Li; Sun, Guangai; He, Duanwei
ABSTRACT: We analyzed the compression process of the centrally caved Bridgman-anvil cell by a simplified mechanics model and proposed that the pressure limitation for a given configuration is governed by the compressibility and compression ratios (V0 /V) of the gasket and sample. Then we replaced the middle part of the sample that is prone to undergo plastic deformation with a diamond plate, which will obviously change the stress state of the sample and gasket. The results of ex situ and in situ pressure testing experiments show that this way doubles the efficiency of the pressure generation and largely expands the pressure limitation. The pressure of sample Ni can reach 29.4 GPa in the double toroidal sintered-diamond anvil cell with a sample volume of 17 mm 3 even at the loading force of 1500 kN.